Drinking water quality status in Malaysia: a scoping review of occurrence, human health exposure, and potential needs - Praveena, Sarva Mangala; Aris, Ahmad Zaharin; Hashim, Zailina; Hashim, Jamal Hisham (Springer Nature Limited, 2023)
BACKGROUND: Like other countries, surface water degradation in Malaysia is linked with common global issues. Although different aspects of drinking water suitability have been examined, the overall understanding of drinking water quality in Malaysia is poor. OBJECTIVE: Hence, the present review aims to provide an understanding of drinking water (tap water, groundwater, gravity feed system) quality and its potential implications on policy, human health, and drinking water management law and identification of potential direction of future drinking water research and management needs in Malaysia. METHODS: This study utilized a scoping review method. PRISMA Extension for Scoping Reviews was used for search strategy. Relevant studies were screened using the selected keywords and databases. RESULTS: A total of 26 drinking water quality studies involving tap water, groundwater, and gravity feed systems have been selected for review. These studies found that the majority of Malaysian Drinking Water and WHO Drinking Water standards have been met. High levels of Cu, Cd, Fe and Pb were attributable to galvanized plumbing and pipe material corrosion. Variation of fluoride in tap water depends on dosage planning and operational processes of the public water supply. Pollutants (nitrate and ammonia) in groundwater and gravity feed system water have been linked to agricultural practices in rural areas. Microbiological quality in tap water is associated with growing biofilms inside the pipelines while in groundwater is caused by shallow surface events. However, only eight studies have reported about the human risks of chemical pollutants in tap water. IMPACT STATEMENT: The review discusses the state of drinking water quality in Malaysia and its impact on public health. It suggests that policymakers can use this information to improve the quality of drinking water and enforce restrictions, while also raising public awareness about the importance of safe drinking water. The study can guide future research and initiatives in Malaysia, ultimately contributing to efforts to ensure access to clean and dependable drinking water.